Correlation of safety behavior, handover quality, and risk perception: A cross-sectional study among Chinese psychiatric nurses - Liu, Yakun; Teng, Weiyu; Chen, Chen; Zou, Guiyuan (Frontiers in Psychiatry, 2022)
Background Nurses’ safety behaviors played an important role in patients’ safety goal realization, and it varies from person to person. However, less research has explored the safety behavior level of psychiatric nurses and its influencing factors. Thus, this research aimed to assess the level of safety behavior and explore whether risk perception mediated the relationship between handover quality and safety behavior among psychiatric nurses. Methods A total of 186 registered psychiatric nurses in a Chinese hospital were recruited for this study, through the convenience sampling method. Handover quality, risk perception, and safety behavior were measured. Hayes’ PROCESS macro was used to evaluate the mediation of risk perception between handover quality and safety behavior. Results Scores of psychiatric nurses’ safety behaviors were (47.98 ± 7.45), and handover quality and risk perception could predict the variance of nurses’ safety behaviors. Risk perception could partially mediate between handover quality and nurses’ safety behaviors, and the value of the mediating effect was 49.17%. Conclusion Psychiatric nurses’ safety behaviors have a large promotion space. Therefore, healthcare professionals should endeavor to improve the handover quality of psychiatric nurses and decrease their risk perception, thereby promoting nurses’ safety behaviors.